ANALISIS PENGARUH GAYA KEPEMIMPINAN, LINGKUNGAN KERJA TERHADAP KINERJA GURU - Aflachal Muthowah (MIYAH : Jurnal Studi Islam, 2016)
The purpose of this research is to examine and analyze theinfluence of leadership style and work environment on teacher performance inpublic junior high school. The population in this study are all teachers who teachas many as 52 teachers. So the research is a population study as a sample.Data analysis techniques in this study using path analysis (Path Analysis) toanalyze the data obtained. Operated through SPSS 16 program. The result ofanalysis shows that there is a positive influence of leadership style on teacherperformance and there is positive effect of work environment on teacherperformance